Effect of tempered procedures on the crystallization behavior of different positions of cocoa butter products. (15th February 2022) - Liu, Wentao; Yao, Yunping; Li, Changmo
Highlights: Variant density and layer between inner and outer part in under-tempered products. Unsaturated TAGs enrich in the inner part of under-tempered products. Varieties in TAGs at inside and outside of product cause different thermal property. Polymorphism conversion between β′-IV and β-VI crystals occur with oil migration. Abstract: The effects of tempered procedures (well and under-tempered) on the crystalline behaves of cocoa butter were elaborated through detecting crystalline structure and compositions of crystals located at different positions of cocoa butter products in this study. The under-tempered products couldn't form crystalline structures as uniform as the well-tempered ones, whose internal contained more low saturated triacylglycerol and structurally unstable crystals. The low saturated triacylglycerol further created the diverse microstructure and thermal properties between center and outer part of cocoa butter products. During storage, the concentration differences drive migration of low saturated triacylglycerol from center to outer part of the product. Although this reduces the differences in triacylglycerol composition, it results in the polymorphism conversion between β'-IV and β-VI form and the fat bloom formation. This work indicates that the monitor for crystalline properties of different positions in cocoa butter products helps the chocolate industry to control formation of fat bloom.